2023
DOI: 10.1039/d2ra08176h
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and bioactivity of myricetin derivatives for control of fungal disease and tobacco mosaic virus disease

Abstract: A series of myricetin derivatives containing isoxazole were designed and synthesized to control fungal disease and TMV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Half-leaf spot method was employed to investigate the antiviral activity of target compounds on Nicotiana tabacum leaves grown at the same age and TMV (500 µg/mL) [34][35][36][37]. The results are shown in Table 1 and Fig.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Half-leaf spot method was employed to investigate the antiviral activity of target compounds on Nicotiana tabacum leaves grown at the same age and TMV (500 µg/mL) [34][35][36][37]. The results are shown in Table 1 and Fig.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…It possesses a variety of biological activities such as antimicrobial, antioxidant, antimutagenic, anticarcinogenic, anti-inflammatory, antiallergic, analgesic activities and so on, 18,19 and thus has attracted a great deal of attention from researchers. In the previous studies of our group, the derivatives of myricetin were found to possess a variety of biological activities such as anticancer, 20 antiviral, [21][22][23] antibacterial, [24][25][26] and antifungal activities, 27,28 which provides a new idea for the discovery of new green pesticides.…”
Section: Introductionmentioning
confidence: 99%